The relationship between reading strategies and the level of comprehension among students with Autism Spectrum Disorder in a private Arabic school - Toklubok@Hajimaming, Pabiah; Imen, Khelifi; Mustapha, Nik Farhan (University of Malaya, 2024)
It is known that students with autism spectrum disorder face many difficulties in acquiring language skills, including reading skills, due to their delay in language development, but some of them can memorize, a strong memory, and sensitivity to different stimuli. Previous studies have indicated that research on reading strategies has been carried out widely in Western countries, as it has a great potential on discovering the impact of these strategies on comprehension and understanding in this category of students. Therefore, this research will discover the strategies of learning and reading for Arab students with autism spectrum, by adopting the qualitative field approach, and based on this, it was discovered that visual integration and interactive sensory integration have a positive impact on students' comprehension of the reading text, and therefore it is necessary to rely on visual and sensory means in order to raise their level of comprehension.